Living the transformation. Adaptive Reuse as strategy for accessible student housing in Turin (2024)
Finding suitable accommodation is a major hurdle for many off-site students arriving in Turin for the first time. This uncertainty of securing a place to live that fosters a fulfilling university experience is a common challenge for students globally. As a rising student city, Turin offers both advantages and disadvantages in this regard. Local experience suggests securing accommodation before arrival, due to limited options in the fast-moving private rental sector, but not without the risk of encountering fraud. Others opt to look for accommodation upon arrival, albeit this process may take more than a month because of the lack of reliable sources, such as unverified online listings, and limited options in the market. While private apartments are the most common choice, they may not be the most convenient or cost-effective option. International students face additional struggles, with some landlords hesitant to rent to young adults with limited financial backing, lack of guarantors, or language barriers. This often forces students to prioritize affordability over factors like location, accessibility, and amenities, potentially leading to less-than-ideal living situations that hinder their academic experience. This issue extends to the young population who finish their studies and have to find a new place if they decide to stay in the city when scholarships and student benefits are over. The research aims to analyze diverse models and strategies currently being implemented in the city or adopted by the student community, to solve the need for temporary accommodation by comparing their characteristics and identifying actions or elements that can be applied to achieve affordability and integration in the urban context. For future directions, the objective is to apply the best practices and methodologies by designing a hybrid model as a guide for future interventions of this kind. This document will explore a particular case study to test this model as a prototype, then can forward be studied with the aim of replication or evaluation for future projects.